FGF21-dependent alleviation of cholestasis-induced liver fibrosis by sodium butyrate - Yang, Jing; Chen, Lei; Zhao, Shan-Shan; Du, Chuang; Fan, Yi-Zhe; Liu, Hui-Xin; Li, Yongchun; Li, Yong-Zhi (Frontiers in Pharmacology, 2024)
The beneficial effect of FGF21 and sodium butyrate (NaB) on protecting against cholestasis induced liver fibrosis is barely known. We aimed to explore the effect of FGF21 and NaB on bile duct ligation (BDL) induced liver fibrosis.: Wild type (WT) and FGF21 knockout (KO) mice received bile duct ligation (BDL) surgery for 14 days. Liver fibrosis was assessed by Masson's staining, fibrosis marker expressions at mRNA or protein levels. Adenovirus--mediated FGF21 overexpression in WT mice was tested against BDL damage. BDL surgery was performed in WT and FGF21 KO mice either received PBS or NaB administration. The effect of NaB on the energy metabolism and gut microbiota was assessed by stable metabolism detect system and 16S rRNA gene sequencing. Results: BDL induced liver fibrosis in WT mice, accompanied with highly induction of FGF21. Compared to WT mice, FGF21 KO mice showed more severe liver fibrosis induced by BDL. FGF21 overexpression protect against BDL-induced liver fibrosis, as proved by decreasing in α-SMA at both mRNA and protein levels. NaB administration enhanced the glucose and energy metabolism as well as remodeling the gut microbiota. NaB alleviated BDL induced liver fibrosis In WT mice but aggravated in FGF21 KO mice.Conclusions: FGF21 play a key role in alleviating the cholestasis induced liver damage and fibrosis. NaB produce beneficial effect on cholestasis in FGF21 dependent manner. NaB administration can be a novel nutritional therapy to treat cholestasis via boosting FGF21 signaling and regulating gut microbiota.